Hubungan Pengetahuan Gizi dan Perilaku Jajan dengan Status Gizi Siswa Sekolah Dasar - Putri Ayuningthias Logo; Laga Nur, Marselinus; Rahayu, Tanti (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
School children are an age group that is in the phase of growth and development so that the fulfillment of nutrition in school children is very important. The level of knowledge affects the behavior of choosing snacks and nutritional status. This study aims to determine the relationship between nutritional knowledge, snacking behavior and nutritional status of students at SD GMIT Kuanino 3 and SD Negeri Kuanino Kupang City. This type of research is analytic observational with Cross-Sectional research design. Respondents consisted of 74 fourth and fifth grade students who were selected using purposive sampling technique. Data were collected using interview, observation and documentation techniques. The relationship analysis used Chi Square statistical test. The results showed that there was a relationship between nutritional knowledge and students' snacking behavior (p-value = 0.005). The results also showed that there was no relationship between nutritional knowledge and nutritional status (p-value = 0.766). This study is expected to be a reference for schools, parents, and related agencies to increase education about healthy snacks selection, and strengthen supervision of food safety in the school environment.